Comparison of the left and right ventricular size and systolic function of low-risk fetuses in the third trimester: Which is more dominant? - Zhu, Chen; Li, Man; Xu, Cheng-Jie; Ding, Meng-Juan; Xiong, Yu; Liu, Rui; Ren, Yun-Yun (Frontiers in Cardiovascular Medicine, 2023)
Objective: To describe a reproducible approach to quantify ventricular volume calculations utilizing fetalHQ and to explore the differences in size and function of the left and right ventricles in low-risk pregnancy. Methods: This was a prospective cohort study that included 453 low-risk single fetuses (28+0 to 39+6 weeks) for fetal-specific 2D speckle-tracking echocardiography. The association between cardiac ventricular size (end-diastolic length (EDL), end-systolic length (ESL), end-diastolic diameter (ED) and end-systolic diameter (ES)) and systolic function (stroke volume (SV), cardiac output (CO), ejection fraction (EF)) was analyzed, and the left and right ventricular parameter differences were compared. Results: This study showed that the left ventricular EDL and ESL were longer than the right ventricular EDL (2.24 vs. 1.96 cm, P<0.001; 1.72 vs. 1.52 cm, P<0.001). The left ventricular ED and ES were shorter than the right ventricular ED and ES (12.87 vs. 13.43 mm, P<0.001; 5.09 vs. 5.61 mm, P<0.001). The end-diastolic volume of the right and left ventricles was not significantly different (1.89 vs. 1.92 ml, P=0.565), but the end-systolic volume of the left ventricle was smaller than that of the right ventricle (0.71 vs. 1.04 ml, P<0.001). Therefore, the EF, CO and SV of the left ventricle were all higher than those of the right ventricle (EF: 62.69 vs. 46.09%, P<0.001; CO: 167.85 vs. 128.69 ml, P<0.001; SV: 1.18 vs. 0.88 ml, P<0.001). EF does not significantly change with increasing ED-S1 or EDL. SV and CO increased with increasing ED-S1 and EDL (R=0.554-0.705, P<0.001). Conclusion: The left ventricular systolic function (EF, CO, and SV) is greater than the right ventricle function in low-risk fetuses. ED-S1 has a greater impact on cardiac function than EDL.